NILAI-NILAI PENDIDIKAN KARAKTER DALAM BUKU “LUMUT-LUMUT WATULUMBANG” - Ida Ayu Gde Wulandari (GUNA WIDYA: JURNAL PENDIDIKAN HINDU, 2019)
Lumut-Lumut Watulumbang (a book) has a deep self-reflection. The self-reflection is finding in this book by reading all of part of this book. This book teaches us that life is has a mystery that can’t find the final answer. When you think that you have found the answer in your life, there will be a question in yourself, that makes us be doubt for the answer. You will not find the same answer because it depends on the situation and consciousness. So that, in this book, we will find the eternal truth is not outside from ourself, but we can find it in itself. This book teaches us to be consistence to self-contemplation so we will find the Almight-God in ourself. So that’s why, the values of character could find in this book. This book contains of characters value that taken from tattwa of lontar (traditional script). Literary works of Hindu is most of them written on lontar (traditional script) but the writer of this book were packed in a good essays. This book is a good literature as a reference to develop a character bulding that could create an intelligent-character generation. Key-words: self-reflection, consciousness of God, character values